2016
DOI: 10.1182/blood.v128.22.4165.4165
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Arm PHASE 2A Study of NM-IL-12 (rHu-IL12) in Patients with Mycosis Fungoides-Type CTCL (MF) Undergoing Low-Dose TOTAL Skin Electron BEAM Therapy (LD-TSEBT)

Abstract: Multiple treatment modalities are available for MF, but most result in inevitable relapse. Therefore, new treatment strategies that improve response rate and prolong response duration are greatly needed. TSEBT is a highly effective therapy in MF. LD-TSEBT (12 Gy) is much more tolerable than the conventional 36+ Gy dose, thereby allowing for re-treatment; however, LD-TSEBT has a less favorable complete response rate and response duration. Combining LD-TSEBT with immunostimulatory modalities in MF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…The use of low-dose total skin electron beam therapy (LD-TSEBT) has a strong biological rationale to treat cutaneous lymphomas, and ongoing clinical phase II and III trials are combining MOG and LD-TSEBT (NCT04256018; NCT04128072). Additionally, using LD-TSEBT (12 Gy) can stimulate immunity by releasing tumor-specific antigens [71,72]. Notably, MOG does not seem to worsen radiation dermatitis, as evidenced in a retrospective study reviewing 46 courses of radiotherapy administered to 15 consecutive patients with ATLL between 2012 and 2017 [73].…”
Section: Mogamulizumab Results With Combined Treatments In Cutaneous ...mentioning
confidence: 97%
“…The use of low-dose total skin electron beam therapy (LD-TSEBT) has a strong biological rationale to treat cutaneous lymphomas, and ongoing clinical phase II and III trials are combining MOG and LD-TSEBT (NCT04256018; NCT04128072). Additionally, using LD-TSEBT (12 Gy) can stimulate immunity by releasing tumor-specific antigens [71,72]. Notably, MOG does not seem to worsen radiation dermatitis, as evidenced in a retrospective study reviewing 46 courses of radiotherapy administered to 15 consecutive patients with ATLL between 2012 and 2017 [73].…”
Section: Mogamulizumab Results With Combined Treatments In Cutaneous ...mentioning
confidence: 97%
“…Considering the limited clinical benefits of rhIL-12 monotherapy, some researchers have conducted clinical trials with IL-12 combined with other antitumor drugs and techniques, and IL-2 has also been employed as an adjuvant therapy for tumor immunotherapy [ 17 20 ]. To date, clinical trials on the antitumor effect of IL-12 are mainly in the phase I or II stage.…”
Section: Progress In Therapeutic Strategies Of Il-12 Treatment For Camentioning
confidence: 99%
“…In an ongoing clinical study of IL-12 combined with low-dose TSEBT for CTCL, 150 ng/kg of rhIL-12 was injected subcutaneously on day 2 and day 15 post TSEBT (4 Gy/wk, fractionated; up to 12 Gy), followed by maintenance therapy of 100 ng/kg once every 4 weeks for 6 cycles [ 20 ]. The results showed that 5 of the 6 enrolled patients including 4 male patients with an average age of 55 years had evaluable efficacy (of the 5 patients, 1 patient had CR, 2 patients had PR, and 2 patients had stable disease) with a response rate of 60%.…”
Section: Progress In Therapeutic Strategies Of Il-12 Treatment For Camentioning
confidence: 99%
See 1 more Smart Citation
“…Υπάρχουν αυξανόμενες σοβαρές ενδείξεις περί αποτελεσματικής στόχευσης των ογκο-διηθητικών ανοσοκυττάρων (TIL), τροποποίησης του νεοπλασματικού μικροπεριβάλλοντος και αποκατάστασης της ανοσοεπιτήρησης [Leuchte, 2017]. Πολλές ουσίες έχουν δοκιμασθεί και δοκιμάζονται, συμπεριλαμβανομένων, μεταξύ άλλων, των γεμσιταβίνης (ανάλογο πυριμιδίνης) [Pellegrini, 2014], φλουδαραβίνης (ανάλογο πουρίνης) [Quaglino, 2004], δεσιταβίνης (ανάλογο κυτιδίνης) [Jain, 2017], βενδαμουστίνης (ανάλογο αζωθυπερίτη) [Zaja, 2013], πεγκυλιωμένης λιποσωμιακής δοξορουβικίνης (κυτταροτοξικό αντιβιωτικό) και IL-12 [Kim, 2016]. Η μεθοτρεξάτη (ανάλογο φυλλικού οξέος) έχει χρησιμοποιηθεί μόνη ή σε συνδυασμό με άλλους παράγοντες [Aviles, 2015] και δύναται να λειτουργήσει μέσω αυξορρύθμισης του FAS και ενίσχυσης της ευαισθησίας στην απόπτωση [Wu, 2011].…”
Section: θεραπειαunclassified